A founder's heritage: the development of organizational identity. (2nd January 2019) - Boers, Börje; Ljungkvist, Torbjörn
Abstract : The purpose of this paper is to understand how a former family firm strategically makes use of the founder's legacy to preserve its organizational identity. Following a single case study approach, it draws on rich empirical material from semi-structured interviews and extensive archival data. We show how central organizational activities are affected by a founder's heritage long after the formal exit has taken place, illustrating the central, enduring, and distinctive elements of organizational identity a founder has. Regardless of ownership forms, the family company founder's legacy is used to legitimize new owners and maintain the organization's identity. However, centripetal moves complicate the preservation of the organizational identity, whereas a high focus on value leveraging in another ownership form opens up for centrifugal approaches which strengthen the entrepreneurial dimension of organizational identity.